Teratoma-associated and so-called pure Wilms tumour of the ovary represent two separate tumour types with distinct molecular features - Kommoss, Felix; Chong, Anne-Sophie; Apellaniz-Ruiz, Maria; Turashvili, Gulisa; Park, Kay J; Hanley, Krisztina; Valera, Elvis Terci; Deimling, Andreas von; Vujanic, Gordan; McCluggage, W Glenn; Foulkes, William D. (Histopathology, 2023)
Aims Ovarian Wilms tumour (WT)/nephroblastoma is an extremely rare neoplasm that has been reported to occur in pure form or as a component of a teratomatous neoplasm. We hypothesized that teratoma-associated and pure ovarian WT may represent different tumour types with diverging molecular backgrounds. To test this hypothesis, we comprehensively characterized a series of five tumours originally diagnosed as ovarian WT. Methods and Results The five cases comprised three teratoma-associated (two mature and one immature) and two pure WTs. Two of the teratoma-associated WTs consisted of small nodular arrangements of “glandular”/epithelial structures, while the third consisted of both an epithelial and a diffuse spindle cell/blastemal component. The pure WTs consisted of “glandular” structures, which were positive for sex cord markers (including inhibin and SF1) together with a rhabdomyosarcomatous component. The two pure WTs harboured DICER1 pathogenic variants (PVs), while the three associated with teratomas were DICER1 wildtype. Panel-based DNA sequencing of four of the cases did not identify PVs in the other genes investigated. Analysis of the HA19/IGF2 imprinting region showed retention of imprinting in the pure WTs but loss of heterozygosity with hypomethylation of the ICR1 region in two of three teratoma-associated WTs. Furthermore, copy number variation and clustering-based whole-genome DNA methylation analyses identified divergent molecular profiles for pure and teratoma-associated WTs. Conclusion Based on the morphological features, immunophenotype, and molecular findings (DICER1 PVs, copy number, and DNA methylation profiles), we suggest that the two cases diagnosed as pure primary ovarian WT represent moderately to poorly differentiated Sertoli Leydig cell tumours (SLCTs), while the tumours arising in teratomas represent true WTs. It is possible that at least some prior cases reported as pure primary ovarian WT represent SLCTs.
Gesehen am 08.07.2024